El modelo de Rasch : una alternativa para la evaluación educativa en Colombia. (2001)
This paper shows the historical development of the Psychological Testing in Colombia, the State Exam, some of the problems that this discipline has worked in this country, the main problems and weaknesses of the Test Classic Theory and the alternative answers that offers the Item Response Theory (TRI). It presents the models of the TRI, the 3-Param- eters and the Rasch, and two computer programs (BILOG-MG and WINSTEPS) that processes information based on these models. Finally, it points out the advantages of the Rasch related to its power as a mathematical model as well as its practical applicability in the educational measurement.